2010
DOI: 10.1016/j.chemosphere.2010.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical investigations of metals release from submerged coal fly ash using extended elutriate tests

Abstract: a b s t r a c tA storage pond dike failure occurred at the Tennessee Valley Authority Kingston Fossil Plant that resulted in the release of over 3.8 million cubic meters (5 million cubic yards) of fly ash. Approximately half of this material deposited in the main channel of the Emory River, 3.5 km upstream of the confluence of the Emory and Clinch Rivers, Tennessee, USA. Remediation efforts to date have focused on targeted removal of material from the channel through hydraulic dredging, as well as mechanical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 24 publications
4
37
0
Order By: Relevance
“…These dredges pumped the ash from the river bottom through a pipeline into an ash recovery ditch, where the heavier ash particles that settled rapidly were removed by a mechanical excavator for disposal. The remaining water and suspended ash flowed into a sluice channel and mixed with plant process water, then flowed into an ash settling pond that overflowed into a stilling pond for final effluent polishing, and finally was discharged back to the Emory River [2].…”
Section: Introductionmentioning
confidence: 99%
“…These dredges pumped the ash from the river bottom through a pipeline into an ash recovery ditch, where the heavier ash particles that settled rapidly were removed by a mechanical excavator for disposal. The remaining water and suspended ash flowed into a sluice channel and mixed with plant process water, then flowed into an ash settling pond that overflowed into a stilling pond for final effluent polishing, and finally was discharged back to the Emory River [2].…”
Section: Introductionmentioning
confidence: 99%
“…As long as residual ash exists in the Emory River (or downstream), the potential for changes in metal binding and/or changes in speciation leading to differing leaching dynamics exists. Previous work, including studies focused on the Kingston spill site, have shown that river conditions play a major role influencing the bioaccumulation of metals known to be present in coal ash (Ruhl et al 2010;Bednar et al 2010;Ruhl et al 2009;Deonarine et al 2013;Liu et al 2013). Therefore, it is recommended that a holistic long-term monitoring plan be utilized to fully understand the longterm impacts of this spill and minimize risk.…”
Section: Discussionmentioning
confidence: 96%
“…However, the removal of contaminated sediments also comes with significant challenges, including the re-suspension of potential contaminants, measuring effects, and potential changes in metal speciation (Bednar et al 2010;Rowe et al 2002;Gustavson et al 2008). Given the volume of the ash spilled (4.1 million m 3 ), the volume of contaminated sediments dredged (more than 2.6 million m 3 ), and the fluctuations in Emory River discharge during dredging (50-70,000 cfs), issues related to the physical disruption of ashassociated sediments were a concern at the Kingston Fossil spill site.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations